The Effect of Welfare Fulfillment on Kindergarten Teacher Performance: The Mediating Role of Motivation in Tunjungan District, Indonesia - Chilya Sulchaniya; Yuli Kurniawati; Diana Diana (STAI Hubbulwathan Duri, 2025)
Teacher welfare is a crucial factor influencing motivation and performance, especially in early childhood education settings. This study investigates the effect of welfare fulfillment on teacher performance, with work motivation as a mediating variable, among kindergarten teachers in Tunjungan District, Blora Regency. A quantitative ex post facto design was employed, involving a total population of 82 kindergarten teachers through a total sampling technique. Data were collected using validated and reliable questionnaires and analyzed using path analysis in SPSS 25 to test both direct and indirect relationships among variables. The findings revealed that teacher welfare fulfillment significantly influenced work motivation, with a path coefficient of 0.742 (R² = 0.551). Welfare fulfillment also had a direct positive effect on teacher performance, while motivation had a significant effect on performance with a path coefficient of 0.745 (R² = 0.250). The indirect effect of welfare on performance through motivation (0.55) was greater than the direct effect (0.318), confirming the mediating role of motivation. These results suggest that fulfilling teachers’ welfare needs—both material and psychosocial—enhances motivation and, consequently, improves professional performance. The study supports motivational theories such as Maslow’s hierarchy of needs and McClelland’s theory, emphasizing the importance of well-being in educational outcomes. Welfare fulfillment plays a vital role in enhancing teacher motivation and performance. Future studies should explore additional variables and broader contexts to increase the generalizability of the findings.